Ethnic origin and identity in the Jewish population of Israel. Issue 11 (18th August 2019) - Lewin-Epstein, Noah; Cohen, Yinon
ABSTRACT: The paper addresses the multifaceted quality of ethnicity in the Jewish population of Israel by probing into the ethnic categories and their subjective meaning. The analyses utilise data collected during 2015–2016 on a representative sample of Israelis age 15 and older, as part of the seventh and eighth rounds of the European Social Survey (ESS). Hypotheses are developed concerning the relationship between demographically based ethnic origin and national identity, as well as the effect of ethnically mixed marriages on ethnic and national identities. The analyses reveal a strong preference among Jews in Israel to portray their ancestry in inclusive national categories – Israeli and Jewish – rather than more particularistic, ethno-cultural, categories (e.g. Mizrahim, Moroccan, Ashkenazim, Polish, etc). Yet, whether Israeli or Jewish receives primacy differs by migration generation, socioeconomic standing, religion, and political dispositions. While the findings clearly add to our understanding of Israeli society, they are also telling with regard to immigrant societies more generally. First, they reveal a multi-layered structure of ethnic identification. Second, they suggest that ethnic identities are quite resistant to change. Third, ethnically mixed marriages appear to erode ethnic identities and are likely to replace them with national identities.